Características do solo e estrutura fitossociológica de espécies arbóreas em dois cerradões no Triângulo Mineiro - Rodrigues, Renata Ferreira (2009)
The study of cerradões is very important to improve knowledge phytosociological and edaphics characteristics physiognomy that significantly amended and fragmented. Given this reality, the objective of this study was to determine the phytosociological and soil characteristics of two fragments of cerradão located in Araguari and Uberlândia, MG. To achieve the phytosociological survey were sampled in each area all individuals with circumference at breast height (CAP) ≥ 15 cm in 25 plots of 20m x 20m. The percentage of canopy cover was estimated using a spherical densiômetro located in 38 points at the ends of the plots. As for the parameters edaphic, soil was collected from each plot at a depth of 0 to 20 cm in order to determine the pH (H2O), P, K1+, Ca2+, Mg2+, Al3+, Fe3+ and Mn2+, clay, silt, dense sand and fine sand. To verify the relationship between floristic plots was a Detrended Correspondence Analysis (DCA) and the relationship between the variables of soil and the distribution of species using a Canonical Correspondence Analysis (CCA). The soil under Araguari fragment is more clay, shallower and more nutrient content, while in Uberlândia is more gritty, deep and low in nutrients. Whereas the percentage of base saturation and the availability of Ca, the soil of the fragment Araguari was classified as mesotrophic while that of Uberlândia, dystrophic. The cerradão of Uberlândia presented greater coverage of canopy in the two seasons. As for phytosociological parameters in the fragment of Araguari were sampled 1,340 individuals belonging to 90 species, while in Uberlândia, 83 species distributed among the 1,797 individuals sampled. Fabaceae and Vochysiaceae families had the largest number of species in both areas. In Araguari species with the highest importance value were Terminalia argentea, Qualea grandiflora and Myracrodruon urundeuva while in Uberlândia, Sclerolobium paniculatum, Qualea grandiflora and Miconia albicans were the most important. The Shannon diversity index (H') in Araguari was 3.5 nats. individual-1 and Uberlândia 3.2 nats.individual-1. The DCA in Uberlândia showed that most species are distributed in all plots and only a minority is in particular regions of the area. Araguari already demonstrated a more pronounced difference between the most abundant species distributed in the area. The CCA did not allow major conclusions about the interference of soil variables in the distribution of species in Uberlândia, since only K was significantly related. In soil of Araguari characteristics significantly related to the abundance of species were: Mn, Al, Ca, silt and dense sand may have interfered more in the distribution of species. The interaction of species X environment goes beyond the restricted information and requires greater care in interpreting the results. Conclusions on the distribution of species in terms of environmental variables will have better explanations only after studies in different environments with edaphic physiognomies cerradão of like the present study.